Comparative study of fatigue life behaviour of AA6061 and AA7075 alloys under spectrum loadings - Zakaria, Kamarul Ariffin (Elsevier, 2013)
The study aimed to present several fatigue tests under loading sequences, and to compare the fatigue life behaviour between AA6061 and AA7075 alloys subjected to spectrum loadings at room and elevated temperatures. Constant amplitude loading (CAL), high-to-low and low-to-high loading sequences were derived from a real-time variable amplitude loading that captured from an engine mount bracket of a 1300 cc automobile under normal driving conditions. The shortest fatigue life was found under CAL, followed by the high-to-low and low-to-high loading sequences at both room and elevated temperatures with difference between the maximum and minimum cycles ranged from 7% to 84%. Increased testing temperature (from 27 C to 250 C) exponentially decreased the number of cycles by 75- 84%. The effect of loading sequence was more significant at room temperature than at elevated temperature.